The Effect Structure of Assets, Liquidity, Firm Size and Profitability of Capital Structure (Empirical Study on Manufacturing Companies Listed on Indonesia Stock Exchange) - Siti Nurlaela, Nur Indah Kartika Sari, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to examine the effect structure of asset, liquidity, firm size, andprofitability of capital structure at manufacturing companies listed on IndonesiaStock Exchange. This study uses secondary data, which is data obtained fromIndonesian Capital Market Directory 2015 (ICMD 2015), with purposive samplingmethod obtained as many as 156 samples of the company during 2014 and 2015.Data analysis technique used is multiple linear regression analysis. The results ofdescriptive analysis indicate that the structure of assets, firm size and profitabilitydoes not affect the capital structure. Meanwhile, if seen from the significance ofliquidity variables affect the capital structure significantly. The results of this studyindicate that (1) there are variables of asset structure and firm size that have noeffect on capital structure (2) liquidity variables and profitability affecting capitalstructure, (3) structure of asset, liquidity, firm size, and profitability effect on DERwhile 41,3% influenced by other factor not examined in this research.Keywords: Structure of Asset, Liquidity, Firm Size, Profitability, and Capital Structure.